Mining and Social Inclusion in Peru reality or utopia (2011-2013) - Ramírez Miranda, Durga Edelmira (2015)
The study aims to determine whether it is a reality or utopia social inclusion in the Peruvian Mining. The research is applied and descriptive level. The study population comprises the most representative national mining companies, where the survey technique was applied using non-probability sampling intentional in a total of 100 people living in surrounding towns to the mine and in-depth interviews to authorities in the area. The main activities undertaken by mining companies to benefit the community that demonstrates a commitment to the process of inclusion and social development is identified, allowing us to state that social inclusion in the Peruvian mining is not a utopia but a possible reality performed.